Tracking of Internal Granular Progenitors Responding to Valproic Acid in the Cerebellar Cortex of Infant Ferrets - Shiori Kamiya; Tetsuya Kobayashi; Kazuhiko Sawada (Cells, 2024)
Internal granular progenitors (IGPs) in the developing cerebellar cortex of ferrets differentiate towards neural and glial lineages. The present study tracked IGPs that proliferated in response to valproic acid (VPA) to determine their fate during cerebellar cortical histogenesis. Ferret kits were used to administer VPA (200 μg/g body weight) on postnatal days 6 and 7. EdU and BrdU were injected on postnatal days 5 and 7, respectively, to label the post-proliferative and proliferating cells when exposed to VPA. At postnatal day 20, when the external granule layer was most expanded, EdU- and BrdU-single-labeled cells were significantly denser in the inner granular layer of VPA-exposed ferrets than in controls. No EdU- or BrdU-labeling was found in Purkinje cells and molecular layer interneurons. Significantly higher percentages of NeuN and Pax6 immunostaining in VPA-exposed ferrets revealed VPA-induced differentiation of IGPs towards granular neurons in BrdU-single-labeled cells. In contrast, both EdU- and BrdU-single-labeled cells exhibited significantly greater percentages of PCNA immunostaining, which appeared in immature Bergman glia, in the internal granular layer of VPA-exposed ferrets. These findings suggest that VPA affects the proliferation of IGPs to induce differentiative division towards granular neurons as well as post-proliferative IGPs toward differentiation into Bergmann glia.